To solve the equation 2/3(x-4)=-10, we need to isolate the variable x.
First, let's distribute the 2/3 to the terms inside the parentheses:
(2/3)(x-4) = -10
(2/3)x - (2/3)(4) = -10
(2/3)x - 8/3 = -10
Next, let's add 8/3 to both sides of the equation to get rid of the negative term on the left side:
(2/3)x - 8/3 + 8/3 = -10 + 8/3
(2/3)x = -10 + 8/3
Now, we need to find a common denominator for -10 and 8/3, which is 3:
(2/3)x = -10 + (8/3)(3/3)
(2/3)x = -10 + 24/3
(2/3)x = -10 + 8
(2/3)x = -2
Finally, to solve for x, we want to get rid of the fraction 2/3, so we multiply both sides of the equation by its reciprocal, which is 3/2:
(3/2)(2/3)x = (3/2)(-2)
(1)x = -6/2
x = -3
Therefore, the solution to the equation 2/3(x-4)=-10 is x = -3.
to solve the equation 2/3(x-4)=-10 Izzy wants to multiply
1 answer